Estimation of daily sodium and potassium excretion from overnight urine of Japanese children and adolescents - Masayuki Okuda; Keiko Asakura; Satoshi Sasaki (Komiyama Printing Co. Ltd, 2020)
Abstract Background Estimates of daily sodium (Na) and potassium (K) excretion were explicitly biased when using equations for adults. We aimed to develop equations to estimate them using overnight urine from Japanese children and adolescents. Methods The subjects comprised 70 students aged 10.49-15.76 years: validation group, n = 34; and verification group, n = 36. Each subject performed two operations of overnight spot urine (U m) and 24-h urine (U24) sampling. Concentrations of Na, K, and creatinine (Cr) were measured, and anthropometrics were recorded. In the validation group, Na/Cr, and K/Cr (mEq L−1/mg dL−1) in 24-h urine were predicted from their correspondents in overnight urine. Daily Cr excretion (EstCr24; mg d−1) was estimated according to Mage's method. Results In validation, we formulated Na excretion (mg d−1) = 23 × exp (0.2085) × [(Na/CrUm + 1)1.0148 − 1] × 1.078 × EstCr24/10; and K excretion (mg d−1) = 39 × exp (0.0315) × [(K/CrUm + 1)1.3165 − 1] × 1.078 × EstCr24/10. For verification, we compared estimates with the measured 24-h Na excretion 3596 ± 1058 mg d−1, and K excretion 1743 ± 569 mg d−1. The mean biases and intraclass correlations (3, 1) were −131 mg d−1 and 0.60, respectively for Na excretion; and −152 mg d−1 and 0.55 for K excretion. Conclusion We obtained validated equations to estimate daily Na and K excretion with accessible variables such as Na, K, and Cr concentrations of overnight urine, body height and weight, and age for children and adolescents. When using the obtained equations, caution should be paid to small but definite biases and measurement errors.